IOT ENABLED SMART ADVERTISEMENTS RECOMMENDER FOR SHOPPING MARTS - Muhammad Tauseef; Shahrukh Saleem Qureshi (International Journal of Innovations in Engineering Research and Technology, 2024)
Product advertisement is very crucial in a successful business for several reasons, Advertisement helps increase the visibility of a product. With so many products available in the market, effective advertisement ensures that your product stands out and reaches a wider audience. Advertising a product is also a way to build and reinforce brand awareness. Consistent advertisement helps in creating a strong brand image in the minds of consumers, also the consumers will remember and choose their products when making a purchase. Continuous and strategic product advertisement is essential for the long-term success of a business. It helps in maintaining visibility, adapting to market changes, and staying relevant in the eyes of consumers. Product advertisement can indeed present various challenges, and addressing these challenges effectively is crucial for a successful marketing campaign that is 1) Small company budgets can restrict the range and effectiveness of products advertisement activities 2) Evolving consumer preferences and behaviours can make it difficult to predict how to effectively reach your audience 3) If your brand is not well-known, getting attention for your product can be a hurdle 4) Not fully understanding your target audience can lead to ineffective advertisement strategies. However, the Internet of Things (IoT) plays a significant role in product advertisement and overcome the above listed issues by providing innovative ways to enhance customer engagement, streamline marketing efforts, and gather valuable data for targeted campaigns. This Research investigate the real-time product advertisements using IoT devices and allowing different companies businesses to monitor the advertisement campaigns instantly and remotely for targeted products over different marts and different city locations. We achieved successful results on each remote location as well as targeted mart using ESP-8266 WiFi deployed on each product shelf. In this architecture the overall communication held over the http protocol using RestFul API and Arduino.